2009
DOI: 10.1186/1472-6963-9-231
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variation in the management of oesophagogastric cancer patients: a population-based survey

Abstract: BackgroundPrevious evidence indicates potential variation in the quality of care of cancer patients. We aimed to examine whether recent changes in the treatment of oesophagogastric cancers have been distributed equally among different patient subgroups.MethodsWe analysed population-based cancer registry data about the treatment patterning of oesophagogastric cancer (other than oesophageal squamous cell carcinoma) during 1995-2006.ResultsThere were 14,077 patients aged ≥40 years (69% men). There was only limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…We therefore believe that the observed reduction in surgery use most probably reflects improved patient selection because of better staging, by endoscopic ultrasound, and/or CT and functional imaging (PET) scanning 4. Similar decreasing trends in surgery use have been reported for upper gastrointestinal cancers 5. The proportion of patients with ‘unspecified’ lung cancer who were treated by surgery was very small and could not explain the observed decrease in use of surgery.…”
Section: Discussionmentioning
confidence: 53%
“…We therefore believe that the observed reduction in surgery use most probably reflects improved patient selection because of better staging, by endoscopic ultrasound, and/or CT and functional imaging (PET) scanning 4. Similar decreasing trends in surgery use have been reported for upper gastrointestinal cancers 5. The proportion of patients with ‘unspecified’ lung cancer who were treated by surgery was very small and could not explain the observed decrease in use of surgery.…”
Section: Discussionmentioning
confidence: 53%
“…Most studies reported no significant association between pre- or postdiagnosis alcohol consumption and OS (110). However, some studies found a protective effect of alcohol (1116) and one showed an adverse effect (28). We excluded six of these studies from the meta-analysis as follows.…”
Section: Resultsmentioning
confidence: 99%
“…The local area Index of Multiple Deprivation was used as a proxy for socioeconomic status (SES; ref. 28). Age at diagnosis, vital status, and data on tumor characteristics were obtained through the ECRIC.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings echo those of Lyratzopoulos et al . () in respect of chemotherapy treatment for AC. That we were able to better characterise patients in terms of stage and co‐morbidity gives further credence to our findings and the possibility of a social gradient in respect of total resource use.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in the UK also points to differences in the treatment experience of oesophageal cancer patients related to measures of patient deprivation (Lyratzopoulos et al . ). More deprived patients were found to be less likely to receive curative surgery and, in particular, chemotherapy than those from less deprived areas.…”
Section: Introductionmentioning
confidence: 97%